Aldose reductase genetic polymorphism is a risk factor of diabetics retinopathy among type 2 diabetes mellitus in Yogyakarta, Indonesia - Jujuk Anton Cahyono Ahmad Hamim Sadewa Tasmini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Diabetes mellitus (DM) is a metabolic syndrome characterized by hyperglycemia and glucose intolerance, due toinsulin resistance, insulin deficiency, or both. Diabetics retinopathy (DR) is a DM complication due to retinal abnormality,that causes vision reduction and even blindness. The association between DR and aldose reductase C-106T (ALR C-106T) gene polymorphism has been reported in previous studies. This genetic polymorphism increases the sorbitollevel inside erythrocyte and pericyte in the retinal membrane that leads to weakness of retinal capillary vessel andmicroaneurism. The aim of this study was to know the presence of ALR C-106T gene polymorphism and its frequencydistribution among diabetics Javanese patients in Dr. Sardjito General Hospital Yogyakarta, Indonesia. In addition,this study also aimed to analyze the difference of erythrocytes osmotic fragility (EOF) among ALR genotypes in type2 diabetics patients with DR and without DR and to analyze whether ALR genetic polymorphism is a risk factor ofDR in type 2 diabetic patients. This was a case control study that involved 40 diabetics patients with DR as case and40 diabetics patients without DR as control groups. The C-106T ALR gene polymorphism was determined bypolymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) method. Erythrocytes osmoticfragility was analyzed using spectrophotometer. Genotype and allele distributions were analyzed using x2 and otherdata were analyzed using independent t-test and Mann-Whitney, with p<0.05 was considered as significantlydifferent. The results showed that in type 2 diabetics patients with DR, 33 patients (82.5%) were CC homozygoteindividuals and 7 patients (17.5%) were CT heterozygote individuals. In type 2 diabetics patients without DR, 27patients (67.5%) were CC homozygote individuals and 13 patients (32.5 %) were CT heterozygote individuals. Thegenotype and allele distributions were not significantly different between two groups (p=0.121 for genotype,p=0.151 for allele). Odds Ratio of genotype was 2.270 while allele was 2.023. Erythrocytes osmotic fragility of CCgenotype was higher than CT genotype (p=0.047). In conclusion, there was no significant difference between CCand CT genotype distribution among type 2 diabetics patients with and without DR. Erythrocyte osmotic fragility ofCC genotype was higher than CT genotype. C-106T gene polymorphism was a risk factor of DR in type 2 diabeticpatients.Key words : ALR genes – polymorphism - type 2 DM - diabetic retinopathy - erythrocytes osmotic fragility